Jude the obscure : notes - Hardy; Hardy, Thomas, 1840-1928.; Powell, Robert; Walker, Fiona; Franklyn-Robbins, John.; Fox Video (Firm) (Beverly Hills, CA : CBS Fox Video ; London, England: close publishing company limited, 1993)
Based on the Thomas Hardy 1895 novel, that sent shock waves across England with its scathing indictment of Victorian society and the hipocrisy behind its sacred institutions of marriage, education, and religion.
Cat. 4786.
Originally broadcast by the BBC in 1971.
Dramatised by Harry Green ; produced by Martin Lisemore ; directed by Hugh David ; video presentation by Margot Eavis.
Robert Powell, Fiona Walker, John Franklyn-Robbin.
VHS format.
Keywords: England -- Social conditions -- 19th century